Physician Assistance in Dying: A Subtler Slippery Slope - Duffy, Thomas P. (The Hastings Center report, 2014)
Shortly after discharge, my patient's husband called to inform me that his wife had died suddenly the previous evening. The call was not a surprise. I felt she had silently communicated to me that she was taking matters into her own hands, and the quantity of narcotics I prescribed was enough to be lethal if ingested as a single dose. I was aware that this was a possible and perhaps even likely outcome. I could have limited the drug amount, but this would have required that she return frequently to the clinic. I believed that such restrictions were an affront to her dignity and her autonomy. And she could always stockpile her drugs to achieve the same purpose. In the midst of the ongoing contretemps surrounding the legality of physician-assisted death, there is a grey zone of physician complicity. My action in providing my patient with a potentially lethal quantity of narcotics certainly marks me as an assistant, albeit at a remove, in her suicide.